Studi Empiris Perkembangan Crowdfunding Syariah di Indonesia - Roos Nelly; Harianto Harianto; M.Shabri Abd.Majid; Marliyah Marliyah; Rita Handayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
Crowdfunding plays a role in the Indonesian economy in its development. Sharia crowdfunding has become a solution to provide financial services that are accessible to businesses that lack access to banking, especially in Indonesia. Using a literature review, this study aims to describe crowdfunding and show how sharia crowdfunding is developing in Indonesia. The results of the study show that crowdfunding has continued to develop in Indonesia since it was first popular in 2009. Sharia crowdfunding has the potential to benefit the business world in accessing capital, increasing welfare, and general economic growth. Another finding is that the implementation of sharia crowdfunding is divided into four categories; donation-based, reward-based, asset-based and equity-based crowdfunding. Where there are differences between conventional crowdfunding and sharia crowdfunding from the four categories. In addition, sharia crowdfunding is also faced with several future issues that must be faced, such as: public trust in crowdfunding, quality and understanding, contract innovation, partnerships with banks, integration with NBFIs, especially MFIs and being able to develop businesses that have high risk. Keywords: Crowdfunding, Sharia Crowdfunding, Development